2019
DOI: 10.1016/j.annemergmed.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Emergency Departments: What Is Their Role in Emergency Care?

Abstract: Freestanding emergency departments (EDs), health care facilities that offer emergency care without being physically attached to a hospital, are becoming more common throughout the United States. Many individuals propose that these facilities can help alleviate the stress our current emergency care system faces and provide care to people with limited access to traditional hospital-based EDs. We reviewed the current literature on freestanding EDs to investigate whether these facilities are meeting those goals. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As of 2017, between 550 and 600 FSEDs were reported, compared to only 80 in 2007 . FSEDs have been postulated to reduce the burden of crowding on traditional hospital‐based EDs by drawing in lower‐acuity patients and potentially improving access to care in rural areas where financial strain has reduced the number of critical‐access hospitals . A recent analysis of the current state of FSEDs, however, suggests that they may cater to a more affluent patient population rather than address a lack of access to emergency care in underserved areas .…”
Section: Current Available Data and Projectionsmentioning
confidence: 99%
“…As of 2017, between 550 and 600 FSEDs were reported, compared to only 80 in 2007 . FSEDs have been postulated to reduce the burden of crowding on traditional hospital‐based EDs by drawing in lower‐acuity patients and potentially improving access to care in rural areas where financial strain has reduced the number of critical‐access hospitals . A recent analysis of the current state of FSEDs, however, suggests that they may cater to a more affluent patient population rather than address a lack of access to emergency care in underserved areas .…”
Section: Current Available Data and Projectionsmentioning
confidence: 99%
“…Differences in costs in this study are consistent with those demonstrated in previous comparisons of ED to urgent care costs. 6,[10][11][12][13] Our cost savings estimate is likely conservative in that we only accounted for lowacuity visit diversions in our calculation. The capacity for treatment of higher acuity injuries requiring fracture reduction or other procedures was equivocal between the ED and I-Care, which suggests that cost savings could be substantially higher with proper triaging.…”
Section: Discussionmentioning
confidence: 99%
“…6 Further, FSEDs have traditionally tended to locate further from public transit and therefore have catered to affluent populations with options for care other than hospital-based EDs. 3,[7][8][9] UCCs treat the majority of the most common diagnoses seen at FSEDs. 1 With regard to cost, FSEDs and hospitalbased EDs have higher out-of-pocket liabilities for patients compared to UCCs.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Further, FSEDs have traditionally tended to locate further from public transit and therefore have catered to affluent populations with options for care other than hospital-based EDs. 3 , 7 - 9 …”
Section: Introductionmentioning
confidence: 99%